2012
DOI: 10.1177/1947601912458582
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Roles for the Paxillin Family of Proteins in Cancer

Abstract: The paxillin family of intracellular scaffold proteins includes paxillin, Hic-5, and leupaxin, and all have been identified as key regulators of the cellular migration machinery in both 2-and 3-dimensional microenvironments. Herein, we provide insight into the roles of these proteins during tumorigenesis and metastasis, highlighting their functions in cancer initiation as well as tumor cell dissemination and survival. Furthermore, we speculate on the potential of paxillin family proteins as both future prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 148 publications
(221 reference statements)
4
67
0
1
Order By: Relevance
“…Interestingly, our finding that soluble tumor-derived factors decreased paxillin and NRP2 expression in vitro and in vivo is consistent with past reports that have shown that paxillin is decreased in lung, breast and colorectal tumors, among others (Deakin et al, 2012;Salgia et al, 1999;Yang et al, 2010). This seems to be controversial because paxillin expression has also been reported to be elevated in lung, prostate, breast, cervical and other tumors (Deakin et al, 2012;Jagadeeswaran et al, 2008;Mackinnon et al, 2011;Salgia et al, 1999;Sen et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Interestingly, our finding that soluble tumor-derived factors decreased paxillin and NRP2 expression in vitro and in vivo is consistent with past reports that have shown that paxillin is decreased in lung, breast and colorectal tumors, among others (Deakin et al, 2012;Salgia et al, 1999;Yang et al, 2010). This seems to be controversial because paxillin expression has also been reported to be elevated in lung, prostate, breast, cervical and other tumors (Deakin et al, 2012;Jagadeeswaran et al, 2008;Mackinnon et al, 2011;Salgia et al, 1999;Sen et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Paxillin is a multifunctional multidomain focal adhesion adaptor protein that is phosphorylated by Src and focal adhesion kinase (FAK) (Tachibana et al, 1995;Turner et al, 1990), and associates with many other focal adhesion proteins and signaling molecules (Brown and Turner, 2004;Deakin et al, 2012;Hagel et al, 2002;Sero et al, 2012;Turner et al, 1990). It can positively and negatively regulate cell migration depending on whether it is located at the leading edge (Nayal et al, 2006) or tail end (Nishiya et al, 2005) of the cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6, D and E). It is well known that the phosphorylation of paxillin is required for cell adhesion and invasion (34). Therefore, these data suggested that Yes is involved in the invasion activities via the activation of paxillin, a key protein as a downstream target of Yes in G(ϩ) astrocytes.…”
Section: Figure 2 Establishment Of Gd3-positive Cells and Gd3-negatimentioning
confidence: 80%
“…These data are consistent with our observations in 3D that local tension drives protrusion extension and migration and suggest that stress asymmetries play a role in a variety of cell processes in vivo. Because paxillin appears to mediate cellular responses to IF, and it is also known to be involved in tumor progression and metastasis in many types of cancer (44), modulation of paxillin levels or activity could offer a therapeutic strategy for treating metastatic carcinoma. Importantly, in solid tumors, interstitial fluid flow emanates from the vasculature, and consequently, tumor cells in close proximity to blood vessels will be directed via rheotaxis toward the leaky vasculature, which is the point of maximum fluid pressure (45).…”
Section: Discussionmentioning
confidence: 99%